2012
DOI: 10.1177/1470320312448950
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia and angiotensin converting enzyme (ACE) I/D and angiotensin II type-1 receptor (AT1R) A1166C polymorphisms: association with ACE I/D polymorphism

Abstract: Background: The aim of the present study was to investigate the association between angiotensin converting enzyme (ACE) insertion/deletion (I/D) and angiotensin II type-1 receptor (AT1R) A1166C polymorphisms with the risk of preeclampsia and lipid peroxidation in preeclamptic women from Western Iran. Methods: One hundred and ninety-eight preeclamptic women (128 women with mild and 70 with severe forms) and 100 age-and parity-matched controls were enrolled in this case-control study. Results:The presence of D a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 33 publications
2
21
0
4
Order By: Relevance
“…[13,15,17] In addition, the populations of Romania and the United States revealed the associations of DD ACE genotype with the development of preeclampsia. [12,14] Besides, the studies conducted in the populations of India, China, and Colombia, revealed no significant effect of I/D ACE on the development of preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13,15,17] In addition, the populations of Romania and the United States revealed the associations of DD ACE genotype with the development of preeclampsia. [12,14] Besides, the studies conducted in the populations of India, China, and Colombia, revealed no significant effect of I/D ACE on the development of preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] The available data on the relationship between the polymorphism of ACE gene and the risk of preeclampsia development are contradictory. [11][12][13][14][15][16][17][18][19][20] In this regard, further research is needed to study the role of I/D ACE locus in the development of this complication of pregnancy.…”
Section: Original Articlementioning
confidence: 99%
“…It is the presence of pathological alleles in the AGTR1 gene associated with development of vascular disorders including those not related to blood pressure levels [55,56]. There are also data about the absence of rare allele C of SNP 1166 A4C in AGTR1 gene influence on the violation of pregnancy [57].…”
Section: Snps In the Renin-angiotensin Systemmentioning
confidence: 99%
“…This multifunctional protein plays a key role in processes such as regulation of blood pressure, maintain a balance of electrolytes, platelet activation and aggregation, fibrinolysis. ACE protein functionality and features of its expression, associated with the presence of Alu-sequences in the intron, are devoted to a great number of publications [55,56,[60][61][62]. Virtually all studies agree that the presence of variant D (Del), lack of Alu-sequences in the intron of the ACE gene, is associated with atherosclerotic, cardiovascular disorders and the risk of pregnancy violation [29,61,62].…”
Section: Snps In the Renin-angiotensin Systemmentioning
confidence: 99%
“…We are unaware of such studies correlating ACE gene I/D polymorphism with response to antihypertensive in PE as well as GH patients. The choice of ACE gene was based on the reports claiming an association of D allele with a predisposition to PE and the protective role of "II" homozygote [8][9][10]. In a similar study, a single nucleotide polymorphism in endothelial nitric oxide synthase coding gene affecting the nitric oxide (NO) production was correlated with antihypertensive treatment in PE and GH [11].…”
Section: Introductionmentioning
confidence: 99%